An Evaluation of Vancomycin Area Under the Curve Estimation Methods for Children Treated for Acute Pulmonary Exacerbations of Cystic Fibrosis Due to Methicillin‐Resistant Staphylococcus aureus. (29th October 2018) - Stockmann, Chris; Olson, Jared; Rashid, Jahidur; Lubsch, Lisa; Young, David C.; Hersh, Adam L.; Frymoyer, Adam; Ampofo, Krow; Liu, Xiaoxi; Wang, Yuhuan; Sherwin, Catherine M.T.; Zobell, Jeffery T.
Abstract: The prevalence of pulmonary methicillin‐resistant Staphylococcus aureus infections in patients with cystic fibrosis (CF) has increased over the last 2 decades. Two concentrations—a postdistributive and a trough—are currently used to estimate the area under the curve (AUC) of vancomycin, an antibiotic routinely used to treat these infections, to achieve the target AUC/minimum inhibitory concentration of ≥400 mg·h/L in ensuring optimal dosing of this drug. This study evaluated precision and bias in estimating vancomycin AUCs obtained either from a population pharmacokinetic (PK) model by using a single trough concentration or from standard PK equation–based 2‐point monitoring approach. AUCs were either obtained from a single trough concentration–fitted model or derived from a model fitted by 2 concentration points. Children ≥2 years of age with CF received intravenous vancomycin at 2 centers from June 2012 to December 2014. A population PK model was developed in Pmetrics to quantify the between‐subject variability in vancomycin PK parameters, define the sources of PK variability, and leverage information from the population to improve individual AUC estimates. Twenty‐three children with CF received 27 courses of vancomycin. The median age was 12.3 (interquartile range [IQR] 8.5–16.6) years. From the individual vancomycin PK parameter estimates from the population PK model, median AUC was 622 (IQR 529–680) mg·h/L. Values were not significantly different from the AUC calculated using the standard PK equation‐based approach (median 616 [IQR 540–663] mg·h/L) ( P = .89). A standard PK equation‐based approach using 2 concentrations and a population PK model‐based approach using a single trough concentration yielded unbiased and precise AUC estimates. Findings suggest that options exist to implement AUC‐based pediatric vancomycin dosing in patients with CF. The findings of this study reveal that several excellent options exist for centers to implement AUC‐based pediatric vancomycin dosing for patients with CF.